2022
DOI: 10.1186/s12967-022-03389-5
|View full text |Cite
|
Sign up to set email alerts
|

ICH-LR2S2: a new risk score for predicting stroke-associated pneumonia from spontaneous intracerebral hemorrhage

Abstract: Purpose We develop a new risk score to predict patients with stroke-associated pneumonia (SAP) who have an acute intracranial hemorrhage (ICH). Method We applied logistic regression to develop a new risk score called ICH-LR2S2. It was derived from examining a dataset of 70,540 ICH patients between 2015 and 2018 from the Chinese Stroke Center Alliance (CSCA). During the training of ICH-LR2S2, patients were randomly divided into two groups – 80% for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Our research results were in keeping with the previous analysis of stroke-associated pneumonia. The incidence of SAP was about 28.2% 28 . ICH patients with advanced age, more severe neurological impairment at admission, underwent nasogastric tube feeding, and higher NLR values were more likely to encounter SAP 29 31 .…”
Section: Discussionmentioning
confidence: 96%
“…Our research results were in keeping with the previous analysis of stroke-associated pneumonia. The incidence of SAP was about 28.2% 28 . ICH patients with advanced age, more severe neurological impairment at admission, underwent nasogastric tube feeding, and higher NLR values were more likely to encounter SAP 29 31 .…”
Section: Discussionmentioning
confidence: 96%
“…Using prognostic markers, several SAP prediction scores have been proposed, including the A2DS2 score, the 22-point ISAN score, the PNA score, and the ACDD score. The ICH-LR2S2 score has been developed specifically for SAP after acute intracranial hemorrhage [ 19 ]. Comparative internal or external validations of these scores have been performed [ 13 , 20 – 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies, we found that the incidence of pulmonary disease (80.6% vs. 11.1%) and cerebrovascular disease (62.5% vs. 23.5%) was particularly high in the elderly population. In addition, pulmonary [18][19][20] and cerebrovascular [21,22] diseases have been proven to play an important role in the prognosis of ICH patients. A previous study focused on functional outcome after 1 year of ICH [12], and our study demonstrates that CCI, as a sum score weighted according to the presence of various comorbidities, also has an impact on the short-term prognosis of elderly ICH patients.…”
Section: Discussionmentioning
confidence: 99%